2017
DOI: 10.3390/v9080234
|View full text |Cite
|
Sign up to set email alerts
|

An Adenovirus-Vectored Influenza Vaccine Induces Durable Cross-Protective Hemagglutinin Stalk Antibody Responses in Mice

Abstract: Currently licensed vaccines against the influenza A virus (IAV) need to be updated annually to match the constantly evolving antigenicity of the influenza virus glycoproteins, hemagglutinin (HA), and neuramidiase (NA). Attempts to develop universal vaccines that provide broad protection have resulted in some success. Herein, we have shown that a replication-deficient adenovirus expressing H5/M2e induced significant humoral immunity against the conserved HA stalk. Compared to the humoral responses induced by an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 64 publications
(88 reference statements)
1
15
0
Order By: Relevance
“…Furuya et al also showed that interferon (IFN) type‐1 production, induced by formalin inactivated H1N1 and H3N2 WIV vaccine, is mainly based on TLR7‐MyD88 pathway . Regarding the significant role of keeping the structural integrity of protective epitopes during inactivation to develop cross‐protective immune responses, these data may help explain the lower level of induction of cross‐protection by formalin‐treated viruses …”
Section: Inactivation Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furuya et al also showed that interferon (IFN) type‐1 production, induced by formalin inactivated H1N1 and H3N2 WIV vaccine, is mainly based on TLR7‐MyD88 pathway . Regarding the significant role of keeping the structural integrity of protective epitopes during inactivation to develop cross‐protective immune responses, these data may help explain the lower level of induction of cross‐protection by formalin‐treated viruses …”
Section: Inactivation Methodsmentioning
confidence: 99%
“…So that, depending on the type of vaccine, this chemical agent should be removed, diluted, and/or converted into a nontoxic form after treatment, which is a time‐consuming process 32 . On the other hand, viral antigenic epitope alteration based on chemical modifications induced by formaldehyde may lead to undesirable impacts on the antigenicity and efficacy of vaccines 33,34 . For instance, it has been shown that free formaldehyde present in inactivated whole H1N1 vaccine can reduce the induction of monoclonal antibodies (mAbs) against conserved epitopes of influenza virus 33 .…”
Section: Inactivation Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…An adenovirus vector expressing NP and M2 proteins conferred protection from highly virulent H5N1, H1N1, and H3N2 influenza viruses ( 178 ) as well as reduced viral transmission from vaccinated and infected mice to unvaccinated mice ( 178 , 179 ). Furthermore, Kim et al employed a novel approach to inducing cross-reactive immune responses against HA protein by generating recombinant human adenovirus 5 vector encoding full length HA (from H5N1) and four tendem copies of M2e domain (rAdH5/M2e) ( 180 ). Adenovirus vaccine induced antibody-mediated cross-protection against heterosubtypic viruses in mice ( 180 ).…”
Section: Nucleic Acid Platformmentioning
confidence: 99%
“…Furthermore, Kim et al employed a novel approach to inducing cross-reactive immune responses against HA protein by generating recombinant human adenovirus 5 vector encoding full length HA (from H5N1) and four tendem copies of M2e domain (rAdH5/M2e) ( 180 ). Adenovirus vaccine induced antibody-mediated cross-protection against heterosubtypic viruses in mice ( 180 ).…”
Section: Nucleic Acid Platformmentioning
confidence: 99%